2020
DOI: 10.1111/jonm.13000
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ perceptions of systems thinking and safe nursing care: A cross‐sectional study

Abstract: Aim To assess nurses’ perceptions of systems thinking, safe nursing care and the correlation between them. Background Systems thinking and safe nursing care are the key elements of quality improvement approaches, such as accreditation and patient safety programmes. However, these two variables have not been well studied in different health care settings. Methods In this cross‐sectional study, 300 nurses were selected using the stratified random sampling method. The data were collected using a demographic data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 36 publications
(58 reference statements)
5
16
1
Order By: Relevance
“…Our findings showed that nurses who had higher scores on systems thinking had a lower chance for involvement in the occurrence of AEs. This result confirmed the hypothesis that systems thinking increases quality and patient safety (Dolansky & Moore, 2013;Hwang & Park, 2017;Moazez et al, 2020;Niskanen et al, 2016). The results of a study in Iran found a positive association between systems thinking competency and safe nursing care, and a study conducted in South Korea showed that nurses with higher systems thinking had a lower chance to experience AEs (Hwang & Park, 2017;Moazez et al, 2020).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Our findings showed that nurses who had higher scores on systems thinking had a lower chance for involvement in the occurrence of AEs. This result confirmed the hypothesis that systems thinking increases quality and patient safety (Dolansky & Moore, 2013;Hwang & Park, 2017;Moazez et al, 2020;Niskanen et al, 2016). The results of a study in Iran found a positive association between systems thinking competency and safe nursing care, and a study conducted in South Korea showed that nurses with higher systems thinking had a lower chance to experience AEs (Hwang & Park, 2017;Moazez et al, 2020).…”
Section: Discussionsupporting
confidence: 84%
“…In general, the systems thinking is rated as moderate, which is lower than previous studies; the mean score for total systems thinking was 49.45 (SD = 12.10), which is lower than the mean scores for several previous studies, in Iran (63.25, SD = 9.20), in South Korea (54.5, SD = 7.3) and at Johns Hopkins, School of Medicine (61.15, SD = 10.55) (Aboumatar et al, 2012; Hwang & Park, 2017; Moazez et al, 2020). Furthermore, about a quarter of the study participants (24.85%) have high competency for systems thinking, which is slightly higher than a study conducted in Korea (20%) (Hwang & Park, 2017).…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Systems thinking is the conceptual framework of an interdisciplinary domain that helps clarify the behaviour and structure of complex systems (Hossain et al, 2020). Systems thinking is a crucial factor for quality and safety education for nurses (Dolansky & Moore, 2013), occurrence and reporting of adverse events (Hwang & Park, 2017) and ensuring and promoting patient safety across all health care settings (Hwang & Park, 2017; Moazez et al, 2020; Rizany et al, 2018). Systems thinking can be improved by training (Phillips et al, 2018; Sanko et al, 2021), which improve nurses' perception of safety culture and decrease the prevalence of medical errors (Tetuan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%